Editorial - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to the spring 2022 issue of the Scottish Journal of Residential Child Care (SJRCC). This year marks the journal's 20th anniversary. The journal was first published, in hard copy, in autumn 2002 under the leadership of editor emeritus, Professor Andy Kendrick, who has contributed an article to the current issue. We have exciting plans to mark this important milestone in and around the autumn issue.